2021
DOI: 10.37360/blacpma.21.20.5.33
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry and biological properties of Drimys winteriJR et G. Forster var chilensis(DC) A.

Abstract: Drimys winteri JR et G. Forster var chilensis (DC) A. is a tree native to central and southern Chile. Also it found in part of Argentina. It is abundant in wet swampy localities from sea level to an altitude of 1700 m. This tree is sacred for the Mapuche culture; it is used in folk medicine in such as inflammatory and painful processes. Phytochemical studies have demonstrated that this plant contains mainly sesquiterpenes of the drimane type, flavonoids, essential oils, phytosterols and some lignans. These dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Antioxidants are compounds that protect tissues from damage caused by free radicals, which are highly reactive molecules that damage cellular machinery, contributing to aging and the onset of various diseases, Coronado H et al (2015). Muñoz et al (2021) demonstrated that DW_EO significantly reduced AAPH-induced lipid oxidation and spontaneous oxidation in bovine meat relative to the control group, even more effectively than BHT. In addition, a protective effect on protein structure was observed during incubation with DW_EO compared to samples incubated with AAPH.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidants are compounds that protect tissues from damage caused by free radicals, which are highly reactive molecules that damage cellular machinery, contributing to aging and the onset of various diseases, Coronado H et al (2015). Muñoz et al (2021) demonstrated that DW_EO significantly reduced AAPH-induced lipid oxidation and spontaneous oxidation in bovine meat relative to the control group, even more effectively than BHT. In addition, a protective effect on protein structure was observed during incubation with DW_EO compared to samples incubated with AAPH.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
“…It is always in leaf, and from January to June, it blooms. It is a hermaphrodite species ( Munoz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained for antimicrobial activity for DW_EO, show a greater effect on gram-positive bacteria compared to gram-negative bacteria and yeast, highlighted S. aureus (MIC 8 μg/ml), even if it is compare with the effect its major components β-Caryophyllen and γ -Eudesmol (MIC 64 μg/ ml). There are no studies of the DW_EO in the strains, however, the antifungal activity of front phytopathogenic fungi and insecticidal properties has been described (Muñoz et al, 2021). Essential oils (EOs) offer a plethora of bioactivities including antioxidant, anti-mutagenic, and antiproliferative properties.…”
Section: Compound Cyp2c9mentioning
confidence: 99%
“…chilensis, as well as various lignanes such as sesamin, (−) cubebin, and eudesmin. In addition, according to the literature, many flavonoids such as apigenin, luteolin, kaempferol, quercitrin, taxifolin, quercetin, cirsimaritin, fisetin, and astilbin have been reported and isolated but only from bark and leaves of this endemic tree [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…chilensis, as well as various lignanes such as sesamin, (−) cubebin, and eudesmin. In addition, according to the literature, many flavonoids such as apigenin, luteolin, kaempferol, quercitrin, taxifolin, quercetin, cirsimaritin, fisetin, and astilbin have been reported and isolated but only from bark and leaves of this endemic tree [5]. Our group has previously reported on extracts and some pure compounds from various endemic species in Chile that have potent enzymatic inhibitory effects or other bioactivities linked to ameliorating noncommunicable diseases (NCDs) and neurodegenerative diseases and hypertension.…”
Section: Introductionmentioning
confidence: 99%